Pengaruh Motivasi dan Disiplin Kerja Terhadap Kinerja Pegawai Inspektorat Jenderal Kemensos RI - Sabrina Zahra; Aulia Darmawan (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
This study aims to determine the effect of work motivation and work discipline on the performance of employees of the Inspectorate General of the Ministry of Social Affairs of the Republic of Indonesia. In this study using a quantitative method with an associative approach. The population used in this study amounted to 60 employees of the Inspectorate General of the Ministry of Social Affairs of the Republic of Indonesia. Sampling using saturated sampling technique. The data analysis methods used are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, simple linear regression test, multiple linear regression, correlation coefficient analysis (r), determination coefficient analysis, and hypothesis test (t test and f test). The results of the t test show that work motivation obtains a t count value <t table (-0.270 <2.002) and a significant value of 0.788> 0.05, so it can be concluded that Ho1 is accepted and Ha1 is rejected. This means that there is no influence between work motivation and employee performance (Y). Work discipline obtained a calculated t value > t table (8.169 > 2.002) and a significance value of 0.000 < 0.05. Therefore, it can be concluded that Ho2 is rejected and Ha2 is accepted. This means that there is an influence between work discipline and employee performance (Y). Meanwhile, the results of the F-test showed a calculated F value of 37.353 > 3.16 (calculated F value > F table) and a significance value of 0.000 < 0.05. Therefore, it can be concluded that Ho3 is rejected and Ha3 is accepted. This means that there is an influence between work motivation and work discipline on employee performance. The result of the coefficient of determination test, or r-square, is 0.567, indicating that work motivation and work discipline significantly influence employee performance by 56.7%. The remaining 43.3% is influenced by other factors not examined.